Pengaruh Green Advertising, Eco-Label, Environmental Attitude dan Environmental Awareness Terhadap Green Purchasing Behavior pada Konsumen The Body Shop di Kota Banda Aceh - Tiarni, Risa; Nizam, Ahmad (Manajemen Inovasi Bisnis dan Strategi, 2025)
This study aims to examine the influence between green advertising, eco-label, environmental attitude, and environmental awareness on green purchasing behavior among The Body Shop consumers in Banda Aceh. Data was collected using a questionnaire with a sample of 115 respondents who have purchased The Body Shop products. The sampling technique used was purposive sampling. Data analysis was performed using multiple linear regression. The results indicate that green advertising, eco-label, environmental attitude, and environmental awareness have a significant partial effect on the green purchasing behavior of The Body Shop consumers in Banda Aceh. Simultaneously, these four variables also influence green purchasing behavior. The findings are expected to provide valuable insights for both companies and consumers, as well as contribute to a better understanding of the factors influencing green purchasing behavior.Keywords:Green advertising,Eco-label,Environmental attitude,Environmental awareness,Green purchasing behavior